2021
DOI: 10.1016/j.jmoldx.2021.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Clinical CYP2D6 Genotyping Allele Selection

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 93 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Haplotype blocks based on sample-specific linkage disequilibrium (LD) pattern from Haploview v4.1 28 29 were defined for all analysed SNPs according to gene-specific haplotype tables from the PharmVar homepage (https://www.pharmvar.org/gene; supplement 2). Haplotype coverage for CYP2D6 and CYP2C19 aligns with the recommended tier 1 alleles for CYP2D6 and CYP2C19 for 5 of 10 and 2 of 3, respectively 30 31 . From a total of 101 genotyped single markers located within 26 genes, we restricted our analyses to genes affecting pk (n=14), thus including 86 variants.…”
Section: Methodsmentioning
confidence: 59%
“…Haplotype blocks based on sample-specific linkage disequilibrium (LD) pattern from Haploview v4.1 28 29 were defined for all analysed SNPs according to gene-specific haplotype tables from the PharmVar homepage (https://www.pharmvar.org/gene; supplement 2). Haplotype coverage for CYP2D6 and CYP2C19 aligns with the recommended tier 1 alleles for CYP2D6 and CYP2C19 for 5 of 10 and 2 of 3, respectively 30 31 . From a total of 101 genotyped single markers located within 26 genes, we restricted our analyses to genes affecting pk (n=14), thus including 86 variants.…”
Section: Methodsmentioning
confidence: 59%
“…This is not surprising since Naveen (2006) showed that the distribution of CYP2D6*2 is similar between the European and South Asian populations [ 63 ]. The prevalence of CYP2D6*2 is about 28% among Europeans, 12–29% in the Asian populations, and 16–20% in people of African ancestry [ 33 ]. Sistonen (2007) proposed that long-term selective pressure maintains a high frequency of haplotypes encoding a fully functional enzyme, causing a homogeneous geographic distribution of *1 and *2 alleles [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…CYP2D6*10 is a decreased-function allele predominantly found in East and South Asian populations, where its prevalence ranges from 9% to 44%. Its frequency in African populations is between 4–6%, among Europeans < 2% [ 4 , 33 ], and it is also present in the Croatian Roma (6%). According to its prevalence, the Roma from Medjimurje (10%) are closest to the South Asians, especially South Indians [ 63 ], while the Balkan Roma (3%) are closer to European populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations